PENGARUH HOTEL IMAGE, SERVICE QUALITY, DAN PERCEIVED VALUE TERHADAP CUSTOMER SATISFACTION HOTEL BINTANG 5 DI SURABAYA PADA MASA PANDEMI COVID - 19 - Gondokusumo, Michelle; Dewi, S.E., M.M2, Yuli Kartika (PERFORMA, 2023)
The purpose of this research is to analyze the effect of hotel image, service quality and perceived value on customer satisfaction of 5-star hotels in Surabaya in Covid-19 pandemic period. The population in this research is customers of 5-star hotels in Surabaya in Covid-19 pandemic period who are above 17 years old. Sampling technique in this research uses nonprobability sampling. The research sample that is used is 119 respondents. Data collection uses questionnaire through Google Form. Analysis method of this research is quantitative method and to calculate data using SPSS software. Based on data analysis, t-test output explains that hotel image variable has t-count value of 0.735 in which t-count result is smaller than t-table, that is, 1.009 with significant value of 0.464 greater than 0.05 in which H0 is accepted and H1 is rejected so that the hotel image variable does not affect on customer satisfaction, t-test output explains that service quality variable has t-count value of 3.936 in which t-count result is greater than t-table, that is, 1.009 with significant value of 0.000 less than 0.05 H0 is rejected and H1 is accepted, so service quality variable affects significant on customer satisfaction, t-test output explains that value perception variable has t-count value of 4.135 in which t-count result is greater than t-table that is 1.009 with significant value of 0.000 less than 0.05 H0 is rejected and H1 is accepted, so perceived value variable affects significant on customer satisfaction. Thus, it can be concluded that service quality (X2) and perceived value (X3) affect positive and significant on customer satisfaction (Y), while hotel image (X1) does not affect on customer satisfaction (Y).